1999
DOI: 10.1002/1529-0131(199912)42:12<2552::aid-anr7>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Taurine chloramine inhibition of cell proliferation and cytokine production by rheumatoid arthritis fibroblast-like synoviocytes

Abstract: Objective. To examine whether taurine (Tau) or its physiologic chlorinated derivative, taurine chloramine (Tau-Cl), affects proliferation of, and proinflammatory cytokine (interleukin-6 [IL-6] and IL-8) production by, fibroblast-like synoviocytes (FLS) isolated from rheumatoid arthritis (RA) patients.Methods. FLS, isolated from the synovial tissue of 19 RA patients and cultured in vitro for 3-6 passages, were stimulated with the recombinant human cytokines IL-1␤ (1 ng/ml), tumor necrosis factor ␣ (TNF␣; 10 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…Although the detoxification of HOCl/OCI O by Tau-Cl formation has been postulated to account for the protective effects of taurine, more recent studies suggest that Tau-Cl may be a significant biological effector molecule. This is supported by reports that Tau-Cl inhibits production of NO, TNF-␣, and other proinflammatory mediators by activated cells from a variety of different tissues (1,(12)(13)(14)(15)(16)(17). However, the mechanism of Tau-Cl action has not been determined and the effects of Tau-Cl on activated alveolar macrophages have not been reported, except in preliminary form (16).…”
mentioning
confidence: 82%
“…Although the detoxification of HOCl/OCI O by Tau-Cl formation has been postulated to account for the protective effects of taurine, more recent studies suggest that Tau-Cl may be a significant biological effector molecule. This is supported by reports that Tau-Cl inhibits production of NO, TNF-␣, and other proinflammatory mediators by activated cells from a variety of different tissues (1,(12)(13)(14)(15)(16)(17). However, the mechanism of Tau-Cl action has not been determined and the effects of Tau-Cl on activated alveolar macrophages have not been reported, except in preliminary form (16).…”
mentioning
confidence: 82%
“…Synovial fibroblast cell lines were prepared from synovial samples obtained from RA patients as described previously (35). FLS were used for experiments after three to seven passages.…”
Section: Cellsmentioning
confidence: 99%
“…To determine the contribution of endogenous IL-15 in the FLS proliferation, cells were incubated with murine IgG2a (2 g/ml) in medium with 2% FCS for 24 h. Then, medium was replaced with fresh, supplemented with mouse IgG2a (0.5; 2 g/ml) or antagonist of IL-15R␣ (IL-15DM/Fc␥2a) (0.5; 2 g/ml; Ref. 36), and FLS were cultured for an additional 72 h. [ 3 H]TdR (2 Ci/ml; Amersham Pharmacia Biotech, Little Chalfont, U.K.) was added 18 h before the termination of the cell culture, and radioactivity of the samples were measured as described (35).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Taurine was reported to promote the expression of connective tissue growth factor (CTGF) that possesses the ability to repair damaged articular cartilage (Nishida et al 2004;Yuan et al 2007). Several researches demonstrated that taurine and its derivatives could inhibit development of rheumatoid arthritis (Kontny et al 1999;Verdrengh and Tarkowski 2005;Marcinkiewicz and Kontny 2014). On the other side, taurine was found to play an important role in bone mineral density of ovariectomized rats (Kontny et al 1999;Choi and DiMarco 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several researches demonstrated that taurine and its derivatives could inhibit development of rheumatoid arthritis (Kontny et al 1999;Verdrengh and Tarkowski 2005;Marcinkiewicz and Kontny 2014). On the other side, taurine was found to play an important role in bone mineral density of ovariectomized rats (Kontny et al 1999;Choi and DiMarco 2009). All lines of evidence suggest that taurine may affect cartilage growth.…”
Section: Introductionmentioning
confidence: 99%